Structured Farmer Empowerment Through Village Governance Reforms: Pemberdayaan Petani yang Terstruktur Melalui Reformasi Tata Kelola Desa - Kurnawati Pasulle; H. M. Z. Arifin; Ahmad Yani; Deandlles Christover (Academia Open, 2025)
General Background: Farmer empowerment is a key strategy for enhancing rural economic welfare, with village governments serving as primary facilitators of development based on local potential. Specific Background: Loa Pari Village, Kutai Kartanegara Regency, possesses significant agricultural potential; however, farmers’ productivity remains hindered by limited facilities, low participation, and restricted access to information. Knowledge Gap: Research on the role of the Loa Pari Village Government in farmer empowerment is limited, particularly regarding mechanisms, effectiveness, and the challenges encountered. Aims: This study aims to analyze the role of the village government in implementing farmer empowerment programs and to identify supporting and inhibiting factors. Results: Findings indicate that the village government plays an important role in providing facilities, forming farmer groups, and collaborating with external institutions, but implementation remains unstructured due to the absence of standard operating procedures (SOPs), budget limitations, and low farmer participation. Novelty: This study highlights the need for measurable and sustainable support systems for village-based farmer empowerment, emphasizing the importance of SOPs, institutional strengthening, and youth engagement. Implications: The results can serve as a reference for village governments and policymakers to design systematic, participatory, and locally adaptive empowerment models. Highlights: Lack of SOPs hampers structured program implementation. Limited budget and low farmer participation remain key barriers. Collaboration with external agencies supports farmer capacity building. Keywords: Farmer Empowerment, Village Government, Agricultural Development, Institutional Strengthening, Rural Participation